Analysis of the Distribution Pattern and Prophage Types in Candidatus Liberibacter Asiaticus ‘Cuimi’ Kumquat - Wen-Ting Li; Xiao-Feng Teng; Li He; Bin Guan; Cui-Ling He; Jian-Jun Liu; Ke-Ling Chen; Zheng Zheng; Jian He (Plants)
The ‘Cuimi’ kumquat is a unique citrus cultivar known for its thin, crisp pulp and sweet, aromatic flavor. In addition to its use in fresh consumption and processing, this variety exhibits certain medicinal properties. This study aims to investigate the genetic diversity of the Huanglongbing (HLB) bacterium across different tissues of the ‘Cuimi’ kumquat, offering a theoretical basis for understanding the HLB epidemic in Dechang County, Sichuan. The research focuses on the absolute quantification of the HLB bacterium in seven specific tissues of the ‘Cuimi’ kumquat, including new leaves, upper phloem of branches, fruit peduncle, pith, fruit axis, old leaves, and lower phloem of branches. Additionally, the types and contents of prophages were identified in these tissues. In the same diseased branch group, Candidatus Liberibacter asiaticus (CLas) exhibited an uneven distribution, with the highest concentration detected in the pith, significantly surpassing levels found in the stem and leaf tissues (new leaves, upper phloem of branches, old leaves, lower phloem of branches). Infected fruit peduncles and pith slices showed noticeable shrinkage and collapse in the phloem. Prophage analysis indicated that multiple types of prophages could be simultaneously detected within the same infected ‘Cuimi’ kumquat branch. New shoot tissues contained both Type 2 and Type 4 prophages, with a relatively higher abundance of Type 4 and a lower abundance of Type 2. The relative abundance of Type 1 prophage in the fruit tissues was generally higher than in other tissues. CLas primarily accumulates in the fruit tissues of the ‘Cuimi’ kumquat, and the situation in Dechang County suggests that individual trees may be infected with multiple prophage strains simultaneously.